Quản lí hoạt động tổ chuyên môn ở các trường trung học cơ sở quận Bình Thạnh, Thành phố Hồ Chí Minh - Phan , Minh Tiến; Lý , Ái Trân (Tạp chí Giáo dục, 2021)
In the direction of reforming education and implementing 2018 general education curriculum, in secondary schools, professional teams play an important role, contributing to improving the quality and effectiveness of teaching and learning at schools. Therefore, in school management, the issue of managing professional teams’ activities has practical significance, and needs special attention. In this paper, the author used the mixed qualitative and quantitative research method to research and evaluate the current situations and established management measures to improve the performance of professional teams in secondary schools of Binh Thanh district, Ho Chi Minh city in order to contribute to improving the effectiveness of teaching activities in schools.